Structural Tunability and Diversity of Two‐Dimensional Lead Halide Benzenethiolate. Issue 29 (19th March 2020) - Coffey, Aidan H.; Yoo, Pilsun; Kim, Dong Hee; Akriti,; Zeller, Matthias; Avetian, Sona; Huang, Libai; Liao, Peilin; Dou, Letian
Abstract: Two‐dimensional (2D) organic‐inorganic hybrid materials are currently of great interest for applications in electronics and optoelectronics. Here, the synthesis and optical properties of a new type of halide‐organothiolate‐mixed 2D hybrid material, Pb2 X(S‐C6 H5 )3, are reported, in which X is a halide (I, Br, or Cl). Different from conventional lead‐based 2D layered materials, these compounds feature unusual five‐coordinated lead centers with a stereochemically active electron lone pair on the lead atoms and four‐coordinated iodine atoms. The Pb2 X(S‐C6 H5 )3 materials feature an indirect bandgap, strongly emissive long‐lived self‐trap states, and an extremely large Stokes shift. Interestingly, the optical bandgap of the materials can be tuned through variation of the halides; however, the photoluminescence is less sensitive to the composition and is more likely dominated by lead‐sulfur lattice interactions or the lead lone‐pair electrons. Our results support that a halide–organothiolate mixed anion hybrid structure offers a unique platform for discovering new exciting 2D electronic materials. Abstract : A new 2D hybrid material, Pb2 X(S‐C6 H5 )3 (X=I, Br, or Cl), was synthesized and characterized with experimental and computational methods. These materials feature strong absorption, an extremely large Stokes Shift, and long carrier lifetimes. Interestingly, the bandgap can be tuned by choice of halide, with little to no effect on the photoluminescent emission.